UJI BEBAN HORIZONTAL PERKERASAN JALAN SISTEM PELAT TERPAKU TIANG TUNGGAL PADA LEMPUNG LUNAK - Puri, Anas (JURNAL SPEKTRAN, 2019)
HORIZONTAL LOADING TEST ON SINGLE PILE NAILED-SLAB PAVEMENT SYSTEM ON SOFT CLAY ABSTRACT Rigid pavement is not only loaded by gravity loads from wheel pressure and temperature, also by horizontally load related to braking forces. This research is aimed to learn the behaviour of Nailed-slab Pavement System due to horizontal load. The 1 : 1 model of single pile Nailed-slab was considered on soft clay. The slab dimension was 120 cm x 120 cm x 15 cm and a pile with diameter 20 cm and lenght 150 cm was installed under the slab. There was 5 cm lean concrete under the slab. Pile and slab was connected monolitically and improved by thickenning slab 40 cm x 40 cm x 20 cm. Slab deflections were observed for each horizontal loads. Results show that the single pile Nailed-slab has a linear elastic behaviour until load 10.4 kN. Lateral deflection for this load was 0.52 mm. Plastic behaviour was developed after load 10.4 kN which indicated by increasing in the lateral deflection of slab